Posterior Cruciate Ligament Reconstruction With Independent Suture Tape Reinforcement: An In Vitro Biomechanical Full Construct Study - Levy, Bruce A. (Orthop J Sports Med, 2021)
BACKGROUND: Posterior cruciate ligament (PCL) reconstruction is commonly performed to restore joint stability and prevent posterior tibial translation at higher flexion angles. However, persistent knee laxity after reconstruction is often reported. PURPOSE: To biomechanically evaluate the effect of independent suture tape (ST) reinforcement on different PCL reconstruction techniques. STUDY DESIGN: Controlled laboratory study. METHODS: PCL reconstruction using porcine bones and quadrupled bovine tendons was performed using 2 techniques: (1) an all-inside method using suspensory adjustable loop devices (ALDs) in the tibia and femur and (2) a method using an interference screw on the tibial and an ALD on the femoral site. Both were tested with and without an additional ST for 4 groups (n = 8 per group). Each construct underwent biomechanical testing involving 3000 loading cycles in 3 stages. After position-controlled cycles simulating full range of motion, force-controlled loading from 10 to 250 N and then from 10 to 500 N were performed before pull-to-failure testing. Elongation, stiffness, and ultimate strength were evaluated. RESULTS: The highest ultimate load (1505 ± 87 N), a small total elongation (2.60 ± 0.97 mm), and stiffness closest to the native human ligament (156.3 ± 16.1 compared with 198.9 ± 33.5 N/mm; P = .192) was seen in the all-inside technique using ST. Intragroup comparison revealed that reinforcement with ST produced a smaller total elongation for the screw fixation (Screw-ALD, 6.06 ± 3.60 vs Screw-ALD ST, 2.50 ± 1.28 mm; P = .018) and all-inside techniques (ALD-ALD, 4.77 ± 1.43 vs ALD-ALD ST, 2.60 ± 0.97 mm; P = .077), albeit the latter was not significantly different. Elongation for constructs without ST increased more rapidly at higher loads compared with elongation for ST constructs. The ultimate strength was significantly increased only for constructs using the all-inside technique using ST (ALD-ALD, 1167 ± 125 vs ALD-ALD ST, 1505 ± 87 N; P = .010). CONCLUSION: Adding an independent ST to PCL reconstruction led to improvement in the studied metrics by reducing the total elongation and increasing the ultimate strength, independent of the technique used. CLINICAL RELEVANCE: PCL reconstruction using additional ST reinforcement was biomechanically favorable in this study. ST reinforcement in the clinical setting could decrease knee laxity after PCL reconstruction, providing better joint stability and improved functional outcomes.